2023
DOI: 10.3390/ijms24043852
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Three New Antimicrobial Peptides from the Marine Mollusk Nerita versicolor (Gmelin, 1791)

Abstract: Mollusks have been widely investigated for antimicrobial peptides because their humoral defense against pathogens is mainly based on these small biomolecules. In this report, we describe the identification of three novel antimicrobial peptides from the marine mollusk Nerita versicolor. A pool of N. versicolor peptides was analyzed with nanoLC-ESI-MS-MS technology, and three potential antimicrobial peptides (Nv-p1, Nv-p2 and Nv-p3) were identified with bioinformatical predictions and selected for chemical synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Peptides from various sources have shown anticandidal activity against C. albicans. For example, human-based peptides (LL-37, histatin 5, and lactoferrin) [ 26 ], plant-based peptides such as NaD1 from Nicotiana alata [ 27 ], Psd1 from Pisum sativum [ 28 ], marine mollusk-based peptides; Nv-p1, Nv-p2, and Nv-p3 from Nerita versicolor [ 29 ], and the insect peptide Gomesin, Acanthoscurria gomesiana [ 30 ], have been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides from various sources have shown anticandidal activity against C. albicans. For example, human-based peptides (LL-37, histatin 5, and lactoferrin) [ 26 ], plant-based peptides such as NaD1 from Nicotiana alata [ 27 ], Psd1 from Pisum sativum [ 28 ], marine mollusk-based peptides; Nv-p1, Nv-p2, and Nv-p3 from Nerita versicolor [ 29 ], and the insect peptide Gomesin, Acanthoscurria gomesiana [ 30 ], have been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…This method is commonly used for de novo sequencing of peptides to elucidate the structure of AMPs. Rodriguez, A et al (2023) [ 185 ] performed peptide sequencing analysis with NanoLC-ESI−MS/MS for peptides from the marine shellfish. Punginelli, D et al (2023) [ 186 ] demonstrated that nine new peptides were further identified through high-resolution MS analysis and database searches.…”
Section: Application Of Ms In Amps Studymentioning
confidence: 99%
“…More than 3100 AMPs with certain therapeutic potential have been reported in recent decades [ 6 ], which is of particular interest in the steadily progressing age of resistance development [ 7 ]. They can be isolated from different organismic resources, with mollusks representing a prominent phylum in which interesting molecules have been identified and further developed [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Classical AMPs are characterized by a simple physicochemical mode-of-action due to the way that they can assemble into pores of the target biomembrane via interactions through the peptide residue sidechains [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%